DISTRIBUSI DALAM EKONOMI ISLAM Upaya Pemerataan Kesejahteraan Melalui Keadilan Distributif (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
Inequality is a universal problem faced by all modern economic systems. The economic injustice and income inequality of wealth which is the beginning of the emergence of the problem of poverty. The emergence of the concept of thinking about distributive justice in an Islamic economy is motivated by the fact that the economic theories that already exist are not able to resolve the problems of poverty and inequality of income and wealth. Therefore, studies on the distribution of discourse always be attract interest in Islamic economics. This paper describes the concept of distribution in the Islamic economics perspective and analyze the issues of inequality in the distribution system of Indonesia, criticism of the distribution in capitalist economies and concludes with the study of the distribution of Islamic economics in distributive justice as well as the mechanism of distribution in Islam as a solution to the justice and public welfare.